2020
DOI: 10.1038/s41598-020-61670-3
|View full text |Cite
|
Sign up to set email alerts
|

Synergic pro-apoptotic effects of Ferulic Acid and nanostructured lipid carrier in glioblastoma cells assessed through molecular and Delayed Luminescence studies

Abstract: Herein, we assessed the effect of Ferulic Acid (FA), a natural antioxidant with anti-cancer effect, on the human glioblastoma cells through molecular and Delayed Luminescence (DL) studies. DL, a phenomenon of ultra-week emission of optical photons, was used to monitor mitochondrial assessment. The effect of FA loaded in nanostructured lipid carriers (NLCs) was also assessed. To validate NLCs as a drug delivery system for glioblastoma treatment, particular attention was focused on their effect. We found that fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(68 citation statements)
references
References 75 publications
0
68
0
Order By: Relevance
“…In 100 µM Indicaxanthin-treated cells, TG2 staining was slightly higher than controls and it was widely localized in the cytosol. In contrast, in the cells exposed to Aβ(1-42) and Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), Indicaxanthin pre-treatment was able to decrease the number of positive cells for TG2, when compared with the controls. Speci cally, in Indicaxanthin treated OECs and subsequently exposed to Aβ(1-42), TG2 was localized into the nucleus.…”
Section: Total Ros/o 2 − Generationmentioning
confidence: 77%
See 4 more Smart Citations
“…In 100 µM Indicaxanthin-treated cells, TG2 staining was slightly higher than controls and it was widely localized in the cytosol. In contrast, in the cells exposed to Aβ(1-42) and Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), Indicaxanthin pre-treatment was able to decrease the number of positive cells for TG2, when compared with the controls. Speci cally, in Indicaxanthin treated OECs and subsequently exposed to Aβ(1-42), TG2 was localized into the nucleus.…”
Section: Total Ros/o 2 − Generationmentioning
confidence: 77%
“…Previous our researches demonstrated that TG2 is overexpressed in OECs exposed to Aβ(1-42) and its toxic fragment Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and that the treatment with some Growth Factors (GFs) was able to restore its levels to control values [18]. In particular, TG2, a calcium-dependent protein with transamidanting activity, is involved in AD, inducing the formation of insoluble amyloid aggregates that can alter the properties of several proteins [2].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations